Bacteria-Metal Interactions - Saffarini, Daad.; Saffarini, Daad. (Springer International Publishing : Imprint: Springer, 2015)
This book provides a detailed description and analysis of the reduction and metabolism of metals and metalloids by sulfate reducing bacteria. The molecular mechanisms of bacterial resistance to copper are examined as well as extracellular electron transfer and bacterial metal oxide respiration. Furthermore, in this book enrichment, isolation, and physiology of magnetotactic bacteria are discussed. The interactions of bacteria with metals in natural environments and their role in metal cycling have been studied for decades. Advances in studies of bacteria-metal interactions identified numerous important aspects of these interactions, such as bioremediation of metal-contaminated environments, the role of metals in redox reactions and other cellular functions, as well as the role of metals in toxicity and infection. Microbiologists, environmental scientists, and students interested in microbe interactions with metals and their effect on the environment and their application in biotechnology will be interested in the topics discussed in the book.